Analysis of one-pass amplifier efficiency in the resonant lidar emitter - Зарудный, А.А. (Radiotekhnika, 2017)
The methods for calculating efficiency of a dye lamp-pumped one-pass amplifier in the emitter resonance lidar are considered taking into account the effect of noise amplification in the active medium. The calculation results indicate that the main mechanism of radiation energy limitation with the increase in the length of the amplifier active medium is the amplified radiation noise.